The Impact of Authentic Leadership and Emotional Labor on Employee Productivity in the Context of Modern Organizations: An Education Literature Review - Yul Windiya Rini; Helmi Buyung Aulia Safrizal (Universitas Muhammadiyah Enrekang, 2023)
This research discusses the impact of authentic leadership and emotional work on employee productivity in the context of modern organizations through literature studies. This study aims to understand how authentic leadership and emotional labor can influence employee productivity in modern organizations. The method used in this research is a literature study by collecting and analyzing journals, books, and articles related to the chosen theme. In its analysis, this study uses a qualitative approach with content analysis techniques to understand the relationship between authentic leadership, emotional work, and employee productivity. The results of this study indicate that authentic leadership and emotional labor have a positive impact on employee productivity in modern organizations. Authentic leadership can help increase employee confidence and motivation in achieving organizational goals, while emotional labor can help employees deal with stress and maintain high engagement in their jobs. This research has important practical implications for modern organizational management in developing effective leadership strategies and paying attention to the emotional labor aspects of employees to increase productivity and overall organizational performance.